Role of microRNA and Long Non-Coding RNA in Hepatocellular Carcinoma - Gupta, Meenakshi; Chandan, Kumari; Sarwat, Maryam (Current Pharmaceutical Design, 2020)
Hepatocellular carcinoma (HCC) accounts for about 80-90% of all liver cancers and is found to be the third most common cause of cancer mortality in the Asia-Pacific region. Risk factors include hepatitis B and C virus, cirrhosis, aflatoxin-contaminated food, alcohol, and diabetes. Surgically removing the tumor tissue seems effective but a high chance of recurrence has led to an urgent need to develop novel molecules for the treatment of HCC. Clinical management with sorafenib is found to be effective but it is only able to prolong survival for a few months. Various side effects like gastrointestinal and abdominal pain, hypertension, and hemorrhage are also associated with sorafenib, which calls for the unmet need of effective therapies against HCC. Similarly, the genetic mechanisms behind the occurrence of HCC are still unknown and need to be expounded further for developing newer candidates. Since unearthing the concept of these variants, transcriptomics has revealed the role of noncoding RNAs (ncRNAs) in many cellular, physiological and pathobiological processes. They are also found to be widely associated and abundantly expressed in a variety of cancer. Aberrant expression and mutations are closely related to tumorigenesis and metastasis and hence are classified as novel biomarkers and therapeutic targets for the treatment of cancer, including HCC. Herein, this review summarises the relationship between ncRNAs and hepatocellular carcinoma.
Keywords: long non-coding RNA (LncRNA)